2013
DOI: 10.2147/nss.s51907
|View full text |Cite
|
Sign up to set email alerts
|

Obstructive sleep apnea in children: a critical update

Abstract: Obstructive sleep apnea (OSA) in children is a highly prevalent disorder caused by a conglomeration of complex pathophysiological processes, leading to recurrent upper airway dysfunction during sleep. The clinical relevance of OSA resides in its association with significant morbidities that affect the cardiovascular, neurocognitive, and metabolic systems. The American Academy of Pediatrics recently reiterated its recommendations that children with symptoms and signs suggestive of OSA should be investigated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
65
2
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 106 publications
(72 citation statements)
references
References 172 publications
(144 reference statements)
3
65
2
2
Order By: Relevance
“…Elevated pulmonary artery pressure is known to complicate the course of patients without a dedicated subpulmonary ventricle and is common in patients with T21 due to sleep disordered breathing . Not surprisingly, our data highlight the importance of pulmonary vascular “health” for selecting T21 candidates for Fontan completion and the pre‐Fontan hemodynamics indicate similar measures (mPAP, TPG, and PVR) with the control group.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Elevated pulmonary artery pressure is known to complicate the course of patients without a dedicated subpulmonary ventricle and is common in patients with T21 due to sleep disordered breathing . Not surprisingly, our data highlight the importance of pulmonary vascular “health” for selecting T21 candidates for Fontan completion and the pre‐Fontan hemodynamics indicate similar measures (mPAP, TPG, and PVR) with the control group.…”
Section: Discussionsupporting
confidence: 62%
“…Elevated pulmonary artery pressure is known to complicate the course of patients without a dedicated subpulmonary ventricle 18 and is common in patients with T21 due to sleep disordered breathing. [19][20][21] Not surprisingly, our data highlight the importance of to increase with age and body mass index and as a result, pulmonary function may deteriorate over time. 22 Therefore, hemodynamic markers measured at the pre-Fontan evaluation may not necessarily predict the success of a patient with T21 in the Fontan pathway.…”
Section: Discussionmentioning
confidence: 67%
“…OSA is associated with daytime sleepiness [99-102] and sleepiness will promote physical inactivity [103], particularly in those children at risk for obesity, such that it should not be surprising that the degree of daytime sleepiness is exaggerated in obese children with OSA [104]. There is also compelling evidence that OSA promotes the initiation and propagation of both localized and systemic inflammatory processes, such that similar to obesity, OSA is currently viewed as a chronic low-grade inflammatory disease [105-112], In this setting, OSA and obesity may interact and potentiate each other and thus amplify their adverse consequences [113-117]. Recently, in a community based study we aimed to examine the effects of adenotonsillectomy in obese children with polysomnographically diagnosed OSAS, on plasma levels of inflammatory and metabolic markers including interleukin-6 (IL-6), IL-18, plasminogen activator inhibitor-1 (PAI-1), monocyte chemoattractant protein-1 (MCP-1), matrix metalloproteinase-(MMP-9), adiponectin, apelin C, leptin and osteocrin.…”
Section: Obesity and Obstructive Sleep Apnea Syndrome: Bad Bad And mentioning
confidence: 99%
“…8 Children with OSA experience repetitive episodes of increased upper airway resistance culminating in partial or complete intermittent obstruction of the upper airway during sleep, leading to major changes in intrathoracic pressures and recurrent arousals as well as episodic oxygen desaturations and hypercapnia. 9 These events are associated with daytime sleepiness, 10,11 the latter leading to reduced physical activity along with increased appetite particularly for high-fat, highcarbohydrate foods. 12 The cumulative evidence derived from a large number of studies has further confirmed the significant associations between the spectrum of sleep disturbance in the context of sleep disordered breathing and the presence of insulin resistance and altered lipid homeostasis.…”
Section: -7mentioning
confidence: 99%